Observations on Music, Culture, and Politics - Asia, Daniel (Cambridge Scholars Publishing, 2021)
This book brings together the collected writings of Daniel Asia from the last 10 years. The articles, reviews, and essays gathered here originally appeared in noted publications such as The New Criterion and Academic Questions, and as blog entries with the Huffington Post. Topics discussed include classical music, universities, Judaism, politics, and American culture. All essays are presented in clear and elegant non-academic prose, and are often imbued with a wry and delicate sense of humor.